The blue straggler star population in NGC 1261: evidence for a post-core-collapse bounce state - Simunovic, Mirko; Puzia, Thomas H.; Sills, Alison (The astrophysical journal. Part 2, Letters, 2014)
We present a multi-passband photometric study of the Blue Straggler Star (BSS) population in the Galactic globular cluster (GC) NGC 1261, using available space- and ground-based survey data. The inner BSS population is found to have two distinct sequences in the color-magnitude diagram (CMD), similar to double BSS sequences detected in other GCs. These well deﬁned sequences are presumably linked to single short-lived events such as core collapse, which are expected to boost the formation of BSSs. In agreement with this, we ﬁnd a BSS sequence in NGC 1261 which can be well reproduced individually by a theoretical model prediction of a 2 Gyr old population of stellar collision products, which are expected to form in the denser inner regions during short-lived core contraction phases. Additionally, we report the occurrence of a group of BSSs with unusually blue colors in the CMD, which are consistent with a corresponding model of a 200 Myr old population of stellar collision products. The properties of the NGC 1261 BSS populations, including their spatial distributions, suggest an advanced dynamical evolutionary state of the cluster, but the core of this GC does not show the classical signatures of core collapse. We argue that these apparent contradictions provide evidence for a post-core-collapse bounce state seen in dynamical simulations of old GCs.
Gesehen am 01.09.2020